Comparing focused attention meditation to meditation with mobile neurofeedback for persistent symptoms after mild-moderate traumatic brain injury: a pilot study. (23rd August 2020) - Polich, Ginger; Gray, Sarah; Tran, Duc; Morales-Quezada, Leon; Glenn, Mel
ABSTRACT: Primary Objective: This study evaluated whether a meditation practice incorporating mobile neurofeedback (mNF) offers any advantage over a more traditional form of focused attention (FA) meditation in managing persistent symptoms after traumatic brain injury (TBI) (clinicaltrials.gov NCT02615535). Research Design: Pilot randomized clinical trial, exploring feasibility of mNF in TBI. Methods and Procedures: Participants included adults with chronic mood and/or cognitive complaints following mild-moderate TBI. Subjects practiced either FA (n = 10) or mNF (n = 10) meditation 12 minutes daily for 6 weeks. Pre-post intervention difference on the Neurobehavioral Symptom Inventory (NSI) was the primary outcome variable. Secondary outcomes included the Beck Anxiety Inventory (BAI), Beck Depression Inventory-II (BDI-II), amongst other scales and neurocognitive tests. Main Outcomes and Results: No significant pre-post between-group differences were found on the NSI ( p = .838) nor other assessments. In an exploratory analysis combining FA and mNF data, meditation was associated with significant improvements on the NSI ( p = .04), BAI ( p = .012) and BDI ( p = .037). Conclusions: Meditating with neurofeedback does not appear to provide an advantage over meditating on one's own for chronic post-TBI symptoms. Further research on home-based meditation following TBI, whether self-directed or technologically facilitated, is warranted.